2013
DOI: 10.1039/c3ic90023a
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of inorganic solids

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 203 publications
(269 reference statements)
0
2
0
Order By: Relevance
“…Previously, it was reported that the local density approximation + U approach may be suitable to study the correlation effects of the CuXY 2 system due to the presence of transition metal atoms [54,55]. In recent years, hybrid exchange correlation with basis set LANL2DZ has been successfully applied to study various physicochemical properties of metallic as well as chalcopyrite clusters consisting of transition metal atoms [56][57][58][59][60][61][62][63][64][65]. Hybrid functional B3LYP and basis set LANL2DZ are adopted for the optimization of CuXY 2 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Previously, it was reported that the local density approximation + U approach may be suitable to study the correlation effects of the CuXY 2 system due to the presence of transition metal atoms [54,55]. In recent years, hybrid exchange correlation with basis set LANL2DZ has been successfully applied to study various physicochemical properties of metallic as well as chalcopyrite clusters consisting of transition metal atoms [56][57][58][59][60][61][62][63][64][65]. Hybrid functional B3LYP and basis set LANL2DZ are adopted for the optimization of CuXY 2 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Computational methods are important in modeling the structure and physical properties of solids and becoming increasingly valuable complements to experimental and theoretical studies [30,31]. Of these methods, atomistic simulations have been successfully used to optimize the structures of iron oxides, including the distribution of point defects in cation-doped systems by minimizing the lattice energy [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%